Hybridization of employment statuses in domestic and care work : comparison of European Union and Latin American strategies - Hrženjak, Majda (2019)
In 2011 ILO adopted Convention 189 with a view to the adoption of a comprehensive standard for decent work for domestic workers. In this paper the authors compare how two different world regions, Latin America and European Union, within diverse socio-economic contexts, equality standards, labour and care cultures and policies, tackle the issue of regulation of domestic work. The authors analyse recent policy developments and their evaluations in two regions along the lines of Definition of services, Service users, Organisational forms, Employment statuses, Working conditions, Professionalization and Public costs. While many EU states have over the past decade developed specific policies to actively promote the development of the formal market of what is euphemistically called "personal and household services" through the introduction of cash-for-care schemes, vouchers or different socio-fiscal measures in order to diminish informal economy, create new employments and support work and family balance, Latin America took a different route. Many Latin American countries amended their legislations including new incentives (such as tax exceptions, occupational hazards insurances) as well as enforcement mechanisms (such as ex-officio enrolment, and labour inspection) in order to formalize informal arrangements. In the conclusion the paper discusses pros and cons of regional strategies from the perspective of quality of employments for domestic and care workers.